Asymmetric Ring Opening/Cyclization/Retro‐Mannich Reaction of Cyclopropyl Ketones with Aryl 1, 2‐Diamines for the Synthesis of Benzimidazole Derivatives. (4th July 2016) - Xia, Yong; Lin, Lili; Chang, Fenzhen; Liao, Yuting; Liu, Xiaohua; Feng, Xiaoming
Abstract: A highly efficient asymmetric ring‐opening/cyclization/retro‐Mannich reaction of cyclopropyl ketones with aryl 1, 2‐diamines has been realized using a chiral N, N′ ‐dioxide/Sc III catalyst. Benzimidazoles containing chiral side chains were generated under mild reaction conditions in excellent outcomes (up to 99 % yield and 97 % ee ). This method also provides efficient access to chiral benzimidazole‐substituted amide and cycloheptene derivatives.